Updating and amending systematic reviews and systematic maps in environmental management. Issue 1 (December 2016) - Bayliss, Helen; Haddaway, Neal; Eales, Jacqualyn; Frampton, Geoff; James, Katy
Abstract Systematic reviews and systematic maps aim to provide an overview of the best available evidence to inform research, policy and practice. However, like any form of review, they will require updating periodically to ensure that the most recent evidence has been incorporated. Here we outline two types of review revisions as recognised in medicine: updates and amendments. Updates involve a search for new studies, expanding the evidence base through time. Any other change (e.g. in screening or synthesis) or correction to the original report is an amendment. Decisions as to whether/when it is appropriate to undertake an update or amendment must be made on a case-by-case basis, considering issues such as the reliability and scope of the existing review or map, likely volume of new evidence, resources available, and the likely value of including new information. Careful, consistent reporting is necessary to ensure transparency and repeatability, particularly where there are deviations from the original methods, and authors should highlight key advances relative to the original report. Updating environmental systematic reviews and maps will be an increasingly important activity as the numbers of both primary studies and synthetic reports in the literature continue to grow.